A new seven-region flow model for deliverability evaluation of multiply-fractured horizontal wells in tight oil fractal reservoir - Guo, Fanrong (2024)
Deliverability evaluation plays an important role in the reservoir exploitation. In this study, a new seven-region semi-analytical mathematical model considering the influences of fractal, imbibition and non-Darcy flow is proposed to evaluate the deliverability of multiply-fractured horizontal wells in tight oil reservoirs. The Laplace transformation, perturbation method and Stehfest numerical inversion are employed to solve the model. The reliability and accuracy of the analytical solution are verified by the field example. The sensitivity analysis of the major influencing factors on the deliverability is specifically analyzed. The numerical results indicate that the seven-region semi-analytical model can better explain the heterogeneity of fracture network, and its solution can provide an effective algorithm for the deliverability evaluation. It is found that the fractal plays a predominant influence on the productivity of tight oil reservoirs. The larger the fractal dimension and the smaller the fractal index, the higher the accumulative production rate. The imbibition also has an important effect on the deliverability of tight oil reservoirs. As the rising of wetting angle, both daily and accumulative production rates can obviously decrease. The imbibition has a positive impact on the production rate in the water-wet formations, while it has a negative impact on the production rate in the oil-wet formations. Compared with the fractal and imbibition, the threshold pressure gradient has less influence on the production of tight oil reservoirs. There exists a negative correlation between the threshold pressure gradient and the production performance. This work provides a new approach to understand the fractal tight oil reservoirs, which is of great significance for the deliverability evaluation.